Pemanfaatan Media Video Animasi pada Pembelajaran IPS Kelas Rendah untuk Meningkatkan Keaktifan Siswa SD Negeri 0100097 Selawan - Asimatu Zahra; Aqila Luthfi Zahrani; Melani Humairoh; Rizqi Muthia; Claudia Marpaung (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the use of animated video media in Social Studies (IPS) learning in lower grades and describe student engagement during the learning process at SD Negeri 010097 Selawan. This study uses a qualitative approach with a descriptive research type. The research subjects include elementary school teachers and students of SD Negeri 010097 Selawan. Research data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The validity of the data was tested using source and technique triangulation techniques. The results of the study indicate that the use of animated video media in Social Studies learning helps create a more interesting and interactive learning atmosphere. Based on the results of observations and interviews, students showed better attention, were more active in participating in learning activities, were more daring to ask questions, and were more enthusiastic in understanding the material presented. In addition, animated video media helped teachers present Social Studies material in a more concrete and easily understood by lower grade students. Thus, animated video media can be an alternative learning media that supports student engagement in Social Studies learning in elementary schools.